Medical Image Fusion Using Hybrid Wavelet Transform - M. N. Narsaiah, S. Vathsal, D. Venkat Reddy (International Journal of Advanced Science and Technology, 2020)
CT and MRI images are fused based an hybrid dual filter algorithm, Discrete Wavelet Transform (DWT) is used to obtain two approximation, six detailed coefficients of CT and MRI medical images, Laplace filter is used to de-noise the wavelet coefficients, by comparing the approximation as well as detailed coefficients two weight maps obtained and that are serves as an input image, the corresponding approximation coefficients are considered as guided image for Guided Filter (GF), weight maps are smoothed by guided filter, which are known as refined. New approximation and detailed coefficients are obtained by weighted fusion algorithm, the Principle Component Analysis (PCA) technique is applied before obtaining CT and MRI images. To get fused image Inverse Discrete Wavelet Transform (IDWT) is used. Proposed hybrid DWT-PCA technique provides better results compared to the existing algorithm qualitatively and quantitatively.